(untitled) (AUN INTERNATIONAL CONFERENCE, 2025)
This study examines the determinants of agricultural credit market participation among farmers in Kano State, Nigeria. Despite numerous credit initiatives, access remains limited due to financial exclusion and institutional barriers. Using primary data from 576 respondents and employing a binary Logit regression model, the study identifies key factors influencing farmers’ participation in credit markets. The findings reveal that commercialization of farming, access to credit information, bank account ownership, off-farm business activities, and social capital variables such as neighborhood participation and traditional title significantly enhance the probability of credit participation. In contrast, reliance on traditional farming tools reduces access. Ownership of radio or television and residence in urban areas also increase participation, underscoring the role of information and location advantages. The study concludes that information asymmetry and weak institutional frameworks limit credit accessibility. It recommends improving financial inclusion, promoting credit awareness, and strengthening local institutions to facilitate broader and more equitable access to agricultural finance